David Ruggles : A Radical Black Abolitionist and the Underground Railroad in New York City - Hodges, Graham Russell, 1946- (Book collections on Project MUSE., 2010)
David Ruggles (1810-1849) was one of the most heroic--and has been one of the most often overlooked--figures of the early abolitionist movement in America. Graham Russell Gao Hodges provides the first biography of this African American activist, writer, publisher, and hydrotherapist who secured liberty for more than six hundred former bond people, the most famous of whom was Frederick Douglass. A forceful, courageous voice for black freedom, Ruggles mentored Douglass, Sojourner Truth, and William Cooper Nell in the skills of antislavery activism. As a founder of the New York Committee of Vigil.